Product market reforms, labour market institutions and unemployment - Rachel Griffith; Rupert Harrison; Gareth Macartney (Institute for Fiscal Studies (IFS), 2006)
We analyze the impact of product market competition on unemployment and wages, and how this depends on labour market institutions. We use differential changes in regulations across OECD countries over the 1980s and 1990s to identify the effects of competition. We find that increased product market competition reduces unemployment, and that it does so more in countries with labour market institutions that increase worker bargaining power. The theoretical intuition is that both firms with market power and unions with bargaining power are constrained in their behaviour by the elasticity of demand in the product market. We also find that the effect of increased competition on real wages is beneficial to workers, but less so when they have high bargaining power. Intuitively, real wages increase through a drop in the general price level, but workers with bargaining power lose out somewhat from a reduction in the rents that they had previously captured.
Keywords: E24; J50; L50; 330; product market regulation; competition; wage bargaining; unemployment; Wettbewerb; Arbeitslosigkeit; Lohn; Gewerkschaft; Entrepreneurship-Ansatz; Lohnverhandlungen; OECD-Staaten; Ökonometrisches Modell